History Learning Game of the Three-Day Battle Surabaya with Branching Narrative - Himawan, Rantau; Putra, Chrystia Aji; Sihananto, Andreas Nugroho (Komunitas Dosen Indonesia, 2026)
This study presents the development of an educational history game about the Three-Day Battle in Surabaya, designed using a branching narrative approach to enhance students’ engagement and historical understanding. Traditional history learning in Indonesia often relies on memorization and lacks interactive media, leading to low student motivation. To address this issue, the game integrates a decision-based narrative structure that allows players to explore consequences, experience alternative paths, and engage with historical events through meaningful choices. The game was developed using the Unity Engine with iterative refinement involving playtesting and feedback-based adjustments to dialogue flow, minigame mechanics, and visual presentation. The evaluation involved 15 participants and employed the GUESS-18 instrument. The results indicate strong user reception, with high scores in Narrative Understanding and Game Engagement, while Playability and Aesthetics received moderate ratings, highlighting areas for visual and interaction improvements. Despite the short testing duration, the game demonstrated potential to support historical learning by increasing immersion and reinforcing students’ understanding of key events and cause–effect relationships during the Surabaya conflict. This study contributes to the field of educational game development by demonstrating the pedagogical value of branching narratives and providing a practical model that can be adapted to other historical topics in future research.